2007
DOI: 10.1111/j.1651-2227.2007.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exocrine pancreatic function on resting energy expenditure in cystic fibrosis

Abstract: Clinically stable CF patients, who had comparable pulmonary function, exhibited increased REE% only in the presence of exocrine pancreatic insufficiency. REE% strongly correlated with BMI z-scores in pancreatic sufficiency. These findings support the hypothesis that pancreatic rather than pulmonary function may determine nutritional status as well as REE in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
(27 reference statements)
2
16
0
Order By: Relevance
“…The American CF Adult Care Consensus defines FEV 1 ≥70% of predicted value as normal or mild lung dysfunction (10). Additional findings support the notion that genotype and PI may be determinants of REE (7, 11, 12). …”
supporting
confidence: 77%
“…The American CF Adult Care Consensus defines FEV 1 ≥70% of predicted value as normal or mild lung dysfunction (10). Additional findings support the notion that genotype and PI may be determinants of REE (7, 11, 12). …”
supporting
confidence: 77%
“…These studied showed that at rest REE was greater than similar healthy non‐CF patients 51 56 . An additional study also showed REE was also greater than predicted REE compared to the Schofield H‐W equation 57 . Studies also demonstrated that there is a strong correlation between pancreatic sufficiency status and REE.…”
Section: Increased Energy Requirementsmentioning
confidence: 93%
“…Studies also demonstrated that there is a strong correlation between pancreatic sufficiency status and REE. Those patients who were diagnosed as being pancreatic sufficient exhibited normal REE compared to healthy subjects 57 . A longitudinal study in well children in Australia concluded that males typically have a lower REE than females.…”
Section: Increased Energy Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease‐specific risk factors for malnutrition in children with CF include increased REE, chronic inflammation, malabsorption secondary to pancreatic insufficiency, fat‐soluble vitamin deficiencies, CF‐related diabetes, and decreased appetite often related to multiple factors including constipation, reflux, chronic inflammation, and small intestinal bacterial overgrowth . Behavioral feeding problems are also common in patients with CF …”
Section: Cystic Fibrosismentioning
confidence: 99%